2015
DOI: 10.1051/matecconf/20153307001
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to study the effect of heating temperature on prior-austenite microstructure of a Japanese sword

Abstract: Abstract. There is uncertainty about heating temperature of final heat treatment and its effect on microstructure of Japanese sword, since the temperature is controlled entirely by experiences and skills of the swordsmith. This study proposed a novel approach to clarify how heating temperature affects prior-austenite microstructure of a Japanese sword. A fragment of the sword was normalized at 800 o C to recover its initial microstructure. Specimens were cut and quenched, after being reheated at temperatures f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The previous studies have reported the nucleation sites of γ and the possible orientation relationship between the γ and the pearlite constituents. However, the currently obtained knowledge is not sufficient to explain our recent observation, in which the coarse pearlite grains transformed to coarse γ grains and vice versa [9]. It seems that more constraints, which limited the number of nucleation sites and the selection of γ orientations, were involved in the formation of γ from pearlite.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…The previous studies have reported the nucleation sites of γ and the possible orientation relationship between the γ and the pearlite constituents. However, the currently obtained knowledge is not sufficient to explain our recent observation, in which the coarse pearlite grains transformed to coarse γ grains and vice versa [9]. It seems that more constraints, which limited the number of nucleation sites and the selection of γ orientations, were involved in the formation of γ from pearlite.…”
Section: Introductionmentioning
confidence: 63%
“…The growth of this γ is faster in multiple directions so that it often has a coarse globular shape. This nucleation mode along with the selection of unique γ orientation by double-OR relation probably leads to the formation of coarse γ grains, which are often observed in high-C steel with the presence of coarse pearlite structure [9].…”
Section: S 180s 240smentioning
confidence: 98%